The Optimization Performance of Bhabinkamtibmas in Preventing the Aggravated Acts of Burglary in the Legal Area of Police Brebes (Polres Brebes) - Ramadhan, Rayhan Aditya (Indonesian Journal of Police Studies, 2024)
The increasing cases of burglary is causing public disturbance. The objective of this review paper is to discuss solution methods that can be used to solve and identify the factors which affects the effectiveness of the performance of Bhabinkamtibmas in preventing acts of bulglary and describing the effort of optimization performance of Bhabinkamtibmas in preventing the aggravated acts of the burglary cases in legal area of police Brebes. The theory used in this study is the management theory initiated by George R. Terry and the problem-oriented policing initiated by Herman Goldstein, which includes scanning, analysis, response, and assessment. The concepts used are the performance concept, the door-to-door system concept, and the Bhabinkamtibmas concept. This research method used a qualitative approach with case study research. The location of this research is in the jurisdiction of the Brebes Police. Primary data sources were obtained from interviews, observations, and document studies. Data validity was tested by source and technique triangulation. Qualitative data analysis used the interactive model. The conclusion, the performance of Bhabinkamtibmas Brebes Police activities for burglary prevention is still not optimal. In addition, burglary prevention efforts are also less targeted. Thus, the problem-solving measures given are expected to succeed to improve the performance of Bhabinkamtibmas Brebes Police.